2017
DOI: 10.1177/1355819617706720
|View full text |Cite
|
Sign up to set email alerts
|

The impact of adverse childhood experiences on health service use across the life course using a retrospective cohort study

Abstract: ObjectivesThe lifelong health impacts of adverse childhood experiences are increasingly being identified, including earlier and more frequent development of non-communicable disease. Our aim was to examine whether adverse childhood experiences are related to increased use of primary, emergency and in-patient care and at what ages such impact is apparent.MethodsHousehold surveys were undertaken in 2015 with 7414 adults resident in Wales and England using random probability stratified sampling (age range 18–69 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 22 publications
5
71
3
Order By: Relevance
“…While previous research suggests that exposure to ACEs is associated with increased healthcare use (Anda et al, 2008;Bellis et al, 2017;Bonomi et al, 2008;Koskenvuo & Koskenvuo, 2015), after consideration of confounding covariates, the various number and types of ACEs were not predictive of increased non-IBD or IBD-related healthcare use in our study.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…While previous research suggests that exposure to ACEs is associated with increased healthcare use (Anda et al, 2008;Bellis et al, 2017;Bonomi et al, 2008;Koskenvuo & Koskenvuo, 2015), after consideration of confounding covariates, the various number and types of ACEs were not predictive of increased non-IBD or IBD-related healthcare use in our study.…”
Section: Discussioncontrasting
confidence: 86%
“…Healthcare use in relation to ACEs has been investigated in a number of studies. A recent study that investigated general practice (GP) visits, emergency department (ED) attendance, and nights spent in hospital, observed significantly higher odds of healthcare use with increasing numbers of ACEs (i.e., higher ACE score) (Bellis et al, 2017). A study that included women with a history of both physical and/or sexual abuse during childhood revealed that participants exhibited increased relative rates of mental health, physician, hospital, and pharmacy service use relative to women never exposed to physical and/or sexual abuse (Bonomi et al, 2008).…”
Section: Adverse Childhood Experiences: a Chronic Environmental Strementioning
confidence: 99%
“…Comparable estimates are not available for exposure to ACEs which include a broader array of childhood stressors including growing up in a household with domestic violence or with family members with depression. However, Bellis et al [11] report that adults with a history of ACEs have significantly higher odds of frequent primary, emergency, and inpatient care relative to those with zero exposure.…”
Section: Introductionmentioning
confidence: 99%
“…[2] These initial findings continue to be validated by a growing body of evidence demonstrating ACEs as a risk factor for multiple adverse outcomes, [8] ultimately culminating in premature mortality. [11] When totaling the costs of health care, child welfare services, criminal justice involvement, and productivity losses over the lifespan, the lifetime economic burden of childhood adversity exceeds $124 billion yearly. hhs.gov/sites/default/files/cb/cm2015.pdf 2015 and http://childhealthdata.org/ browse/survey/results?q=4783&r=1 2016; both accessed 1/2018).…”
mentioning
confidence: 99%